Solitary Contralateral Adrenal Metastasis of Renal Cell Carcinoma: 68Ga-DOTATATE PET/CT Findings. (16th January 2022) - Filizoglu, Nuh; Ozguven, Salih
Abstract: 68 Ga-DOTATATE PET/CT is an imaging technique used in the diagnosis of neuroendocrine tumors. Since renal cell carcinoma (RCC) expresses the somatostatin receptors, 68 Ga-DOTATATE PET/CT could be used in the surveillance of RCC. However, limited cases showing 68 Ga-DOTATATE uptake in the metastases of RCC have been reported before. Herein, we report a case of a 55-year-old woman with a history of left nephrectomy for clear cell renal cell carcinoma 2 years before, and referred to 68 Ga-DOTATATE PET/CT for the evaluation of adrenal mass. 68 Ga-DOTATATE PET/CT showed intense 68 Ga-DOTATATE uptake on the adrenal mass. Histopathology of the adrenal mass confirmed the diagnosis of clear cell renal cell carcinoma metastasis.